Evolving Tree Algorithm Modifications - Cannella, Vincenzo; Rizzo, Riccardo; Pirrone, Roberto (Intelligent Data Engineering and Automated Learning - IDEAL 2007, 2007)
There are many variants of the original self-organizing neural map algorithm proposed by Kohonen. One of the most recent is the Evolving Tree, a tree-shaped self-organizing network which has many interesting characteristics. This network builds a tree structure splitting the input dataset during learning. This paper presents a speed-up modification of the original training algorithm useful when the Evolving Tree network is used with complex data as images or video. After a measurement of the effectiveness an application of the modified algorithm in image segmentation is presented.